1997
DOI: 10.1046/j.1365-2648.1997.1997025908.x
|View full text |Cite
|
Sign up to set email alerts
|

Family members’ experiences of their role in a hospital: a pilot study

Abstract: The purpose of the study is to explore the experiences of family members in their role of relative in a situation where a next of kin has been admitted to hospital. The questionnaire was used in data collection. The data reported here are from a pilot study. The sample consisted of 70 family members of patients receiving treatment on the neurological wards. It was found that family members spent a lot of time at their relative's bedside, most of them up to several hours a day. The daily routines of families an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 17 publications
4
83
0
2
Order By: Relevance
“…This finding is confirmed by other studies. 9,13,17,33 This hope is based on successes seen during the treatment, which encourage the next of kin to forget the previous diagnosis and prognosis, and lend them a "false" hope. Their interpretation of the information is that the ill person will be cured.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is confirmed by other studies. 9,13,17,33 This hope is based on successes seen during the treatment, which encourage the next of kin to forget the previous diagnosis and prognosis, and lend them a "false" hope. Their interpretation of the information is that the ill person will be cured.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted by Åstedt-Kurki et al, they reported various emotional symptoms and feelings of shock induced by illness of a family member in 50% of cases; negative psychological symptoms such as depression and grief were reported in 71% of families [25]. Widayanti stated that parents of children with thalassemia suffer tremendously from provision of daily life-long care for their child [26].…”
Section: Immersion In Sufferingmentioning
confidence: 99%
“…Support is considered to be an important activity in nursing and may include practical, emotional, informational and instrumental support for both patients and their families. Patients' families may require information and education support, emotional support, participation in decisionmaking, and being provided with appropriate amenities and facilities (Astedt-Kurki et al 1997;Astedt-Kurki et al 1999). …”
Section: Introductionmentioning
confidence: 99%